Silicone Granulomas in the Orbit following Breast Implant Rupture: Case Report - Elin Bohman; Rikard Linderoth; Sara Jonmarker Jaraj; Gustav Stålhammar; Eva Dafgård Kopp (Case Reports in Ophthalmology, 2024)
Introduction: A known but uncommon complication following breast augmentation with silicone implants is the rupture of these implants and subsequent silicone migration through the lymphatic system. Exceptionally, there are sporadic instances of silicone granulomas forming in distant, non-lymphatic sites, posing diagnostic and management challenges in clinical practice. Case Presentation: A 56-year-old woman presented with slowly progressive diplopia and photosensitivity during the past 12 months. Ophthalmic examination revealed restriction of movement in all gazes in the right eye. Investigation with magnetic resonance imaging and positron emission tomography-computed tomography showed enlarged superior lateral and inferior rectus muscles in the right orbit, and a diffusely enlarged lacrimal gland in the left orbit, as well as a ruptured silicone breast implant on the right side. In addition, multiple enlarged lymph nodes were found throughout the body, as well as a mass in the internal oblique muscle of the abdominal wall. Fine-needle aspiration biopsy of the axillary lymph node and surgical biopsy of extraocular muscles confirmed a diagnosis of silicone granulomas. The patient received anti-inflammatory treatment with intravenous steroids but with no effect on symptoms. Conclusions: This case illustrates a rare instance of silicone dissemination from a ruptured breast implant leading to granuloma formation in multiple organs, including the orbit. Notably, the spread of silicone appeared to occur through both lymphatic and hematogenous routes. This finding underscores the importance of considering silicone granulomas in the differential diagnosis of orbital lesions for patients with a history of silicone implants.